Factors associated with the consumption of chlorine dioxide to prevent and treat COVID-19 in the Peruvian population: a cross-sectional study - David R. Soriano-Moreno; Daniel Fernandez-Guzman; Fabricio Ccami-Bernal; Cristhian Rojas-Miliano; Wendy Nieto-Gutierrez (BMC, 2021)
Abstract Background Chlorine dioxide has been promoted as an alternative for the prevention and treatment of COVID-19, especially in Peru, despite the lack of evidence to support its efficacy. This study aimed to evaluate the factors associated with chlorine dioxide consumption in the Peruvian population. Methods Analytical cross-sectional study. An adult Peruvian population was evaluated where chlorine dioxide consumption was divided into two groups according to the purpose of use: as prevention (individuals without COVID-19 history) and as treatment (individuals with COVID-19 history). The associated factors in each group were evaluated using Poisson regressions with the bootstrapping resampling method. Results Of 3610 participants included, 3213 reported no history of COVID-19, and 397 had been infected. The prevalence of chlorine dioxide consumption to prevent or treat COVID-19 was 8 and 16%, respectively. Factors either positively or negatively associated with chlorine dioxide consumption for prevention were male sex (aPR: 1.36; 95% CI: 1.09-1.71), being an adult or older adult (aPR: 0.54; 95% CI: 0.35-0.82), having a health sciences student within the family unit (aPR: 1.38; 95% CI: 1.02-1.87), using medical information as the main source of information of COVID-19 (aPR: 0.57; 95% CI: 0.40-0.80), having comorbidities for COVID-19 (aPR: 1.36; 95% CI: 1.01-1.82), considering COVID-19 dangerous and deadly (aPR: 0.57; 95% CI: 0.45-0.74), using medications (aPR: 1.59; 95% CI: 1.25-2.06) and plants to prevent COVID-19 (aPR: 1.69; 95% CI: 1.21-2.36), considering chlorine dioxide ineffective (aPR: 0.18; 95% CI: 0.18-0.24), and being uninformed of its efficacy (aPR: 0.21; 95% CI: 0.16-0.28). In addition, factors associated with chlorine dioxide consumption for treatment were considering COVID-19 dangerous and deadly (aPR: 0.56; 95% CI: 0.33-0.96), considering chlorine dioxide ineffective (aPR: 0.22; 95% CI: 0.12-0.42), and being uninformed of its efficacy (aPR: 0.15; 95% CI: 0.07-0.32). Conclusions The prevalence of chlorine dioxide consumption to treat COVID-19 was higher than prevent. It is important to apply information strategies, prioritizing population groups with certain characteristics that are associated with a higher consumption pattern.